PENGARUH PEMBERIAN AIR REBUSAN KACANG HIJAU TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA PEKERJA BAGIAN KANTOR DI RS.GRANDMED - Jul Asdar putra samura; Delita Br Panjaitan; Raisha Octavariny; Sri Melda Br Bangun; Eka Wulandari (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
Hemoglobin is a protein that is rich in iron. The function of Hb in the blood is to carry oxygen to the lungs, to the tissues and to carbon dioxide. Efforts to increase hemoglobin levels are related to the intake of foods containing iron, one of which is the provision of green bean cooking water. The purpose of this study was to determine the effect of giving mung bean boiled water to an increase in hemoglobin levels in office workers at Rs.Grandmed Lubuk Pakam. This research design with one group pre test-post test. The population in this study were employees of Rs.Grandmed. The number of research samples were 48 workers for the total sampling. Data analysis using paired t-test. The results showed that the HB level of workers before giving green bean cooking water was not normal, namely 39 (81.3%) respondents with an average of 1.81. The HB levels of workers after giving green bean boiled water were all normal HB categories, namely as many as 48 (100%) respondents with an average of 1.00. Data analysis using pre-test and post-test giving green bean boiled water in the experimental group showed results where the p value was 0.000, the value was 0.000 <0.05, so it could be said that there was a significant difference between the pre-test and post-test values. hypothesis is accepted. The conclusion of this study is that there is an effect of giving mung bean boiled water to an increase in hemoglobin levels in office workers at the Grandmed Lubuk Pakam Hospital. It is hoped that the hospital leadership will educate the workers that green bean cooking water can be used as an alternative to increasing hemoglobin levels.